Fabrication of Coupled Resonator Devices for All-optical Switches using As2S3 - LE DUY KHANH (The Graduate School, Ajou University, 2015)
Chalcogenide glasses are good candidate materials for all-optical signal processing devices due to advantages such as high ultrafast third-order non-linearity, low two-photon absorption and broad infrared transparence. Recently, the fabrication of high performance planar optical waveguides, grating and photonic crystal structures from chalcogenide glasses has been paid more attention. In the first part of this thesis, methods for fabrication of As2S3 chalcogenide nanostructure devices are presented including thin-film deposition, photolithography and e-beam lithography for pattern defining, and dry etching for pattern transfer. The annealing treatment at temperature of 130 0C was applied for as-deposited films to avoid the surface degradation and improve the quality of thin-films. For fabrication of microstructures (e.g. optical waveguides), the photolithography technique was used to prepare the waveguide patterns on the As2S3 films prior to dry etching. On the other hand, another lithography technique such as electron-beam lithography was used to fabricate the nanostructure devices (e.g. photonic crystal structures). Finally, for the pattern transfer of desirable structures into As2S3 films, dry etching was carried out with CHF3 gas. The smooth and vertical sidewalls of both waveguides and photonic crystal structure devices were obtained. In the second part of this thesis, the thin-film solar cells based on copper indium gallium selenium (CIGS) material using both single and dual grating structures were introduced in the numerical study. To enhance the absorption efficiencies in those thin-film solar cells, the surface plasma polaritons (SPPs) resonances were introduced. The iii performance analysis of those solar cells were determined by using the rigorous coupled wave analysis (RCWA) based commercial software. The parametric scan method was used to optimize the absorption efficiency for single structures, which are the bottom and top grating structures. For the dual grating structures, the particle swarm optimization (PSO) method was utilized to obtain the ultra broadband absorption spectrum in range from 300 nm to 1200 nm.
학위논문(박사)--아주대학교 일반대학원 :전자공학과,2015. 2
Keywords: As2S3; Fabrication